RIOK-1 Is a Suppressor of the p38 MAPK Innate Immune Pathway in Caenorhabditis elegans - Chen, Yi-Wei; Ko, Wen-Chien; Chen, Chang-Shi; Chen, Po-Lin (Frontiers in Immunology, 2018)
Innate immunity is the primary defense mechanism against infection in metazoans. However, aberrant up-regulation of innate immune signaling pathways can also be detrimental to the host. The p38 MAPK/PMK-1 innate immune signaling pathway has been demonstrated to play essential roles in cellular defenses against numerous infections in metazoans, including Caenorhabiditis elegans. However, the negative regulators that maintain the homeostasis of this important innate immune pathway remain largely understudied. By screening a focused RNAi library against the kinome of C. elegans, we identified RIOK-1, a human RIO kinase homolog, as a novel suppressor of the p38 MAPK/PMK-1 signal pathway. We demonstrated that the suppression of riok-1 confers resistance to Aeromonas dhakensis infection in C. elegans. Using qRT-PCR and riok-1 reporter worms, we found the expression levels of riok-1 to be significantly up-regulated in worms infected with A. dhakensis. Our genetic epistasis analysis suggested that riok-1 acts on the upstream of the p38 MAPK/pmk-1genetic pathway. Moreover, the suppression of riok-1 enhanced the p38 MAPK signal, suggesting that riok-1 is a negative regulator of this innate pathway in C. elegans. Our epistatic results put riok-1 downstream of skn-1, which encodes a p38 MAPK downstream transcription factor and serves as a feedback loop to the p38 MAPK pathway during an A. dhakensis infection. In conclusion, riok-1 is proposed as novel innate immune suppressor and as a negative feedback loop model involving p38 MAPK, SKN-1, and RIOK-1 in C. elegans.